The solvent effect of ethanol and n-hexane on the hydrolysis of triolein and tributyrin by Candida cylindracea lipase - Koc, A.; Ozer, D.; Ekiz, H. I. (Elsevier Science Bv, 2009)
[Abstract Not Available]